Advances in Food Allergy Immunotherapy: Current Strategies and Role of Antibodies Isotypes - Yolanda Garcia-Carmona; Maria A. Curotto de Lafaille (Cells, 2025)
Food allergies result from dysregulated immune responses to dietary antigens. IgE antibodies are key in triggering allergic reactions through binding to high-affinity receptors on mast cells and triggering mast cell activation when crosslinked by allergens. In contrast, IgG antibodies—particularly IgG4—are linked to immunomodulation and tolerance. Allergen-specific memory B cells, especially IgG1+ cells, undergo class-switching to IgE, and IgE plasma cells underlie allergy persistence. Although there is no cure, allergen-specific immunotherapy (AIT) aims to achieve sustained unresponsiveness by gradually increasing allergen exposure. Oral immunotherapy (OIT), a form of AIT, induces a shift from a TH2-skewed response to a more regulated immune profile, characterized by a switch from IgE to IgG4 and IgA isotypes. This review outlines current insights into AIT’s cellular and humoral mechanisms, with implications for improving long-term outcomes and developing predictive biomarkers.